Pengembangan Media Pembelajaran Berbasis Buku Digital Elektronic Publication (Epub) Menggunakan Software Sigil pada Mata Kuliah Pemrograman Dasar - Rasyid Hardi Wirasasmita; Muhammad Zamroni Uska (Jurnal Pendidikan Informatika (EDUMATIC), 2017)
This study aims to develop the learning media in basic programming courses and know the feasibility of learning media of electronic book publication (epub) using software sigil. This research uses research and development approach (Research and Development). The place of this research in the department of Informatics Education, Hamzanwadi University. The object of this research in the form of epub media digital book learning using sigil software in basic programming course. This research is included in the type of Research and Development (R D). Data collection techniques used in this study is a questionnaire method. Questionnaire is used to collect data about the feasibility of learning media made and will be answered by respondents related among others: material experts, media experts, users of instructional media and student responses. The method used to analyze the data is disclosed in the distribution of the five scale scores to the predetermined rating scale category. From the research result, among others: material expert test obtained score 3.53 with good category, media expert test obtained score 4.02 with good category, score of student response 4,03 with good category, so epub learning media digital book using sigil software at basic programming courses are appropriate for use in teaching and learning activities.